Attenuation of fibroblast activation and fibrosis by adropin in systemic sclerosis - Liang, Minrui; Dickel, Nicholas; Györfi, Andrea Hermina; SafakTümerdem, Bilgesu; Li, Yi Nan; Rius Rigau, Aleix Rius; Liang, Chunguang; Hong, Xuezhi; Shen, Lichong; Matei, Alexandru-Emil; Trinh-Minh, Thuong; Tran-Manh, Cuong; et al. (Science Translational Medicine, 2024)
Fibrotic diseases impose a major socioeconomic challenge on modern societies and have limited treatment options. Adropin, a peptide hormone encoded by the energy homeostasis–associated (ENHO) gene, is implicated in metabolism and vascular homeostasis, but its role in the pathogenesis of fibrosis remains enigmatic. Here, we used machine learning approaches in combination with functional in vitro and in vivo experiments to characterize adropin as a potential regulator involved in fibroblast activation and tissue fibrosis in systemic sclerosis (SSc). We demonstrated consistent down-regulation of adropin/ENHO in skin across multiple cohorts of patients with SSc. The prototypical profibrotic cytokine TGFβ reduced adropin/ENHO expression in a JNK-dependent manner. Restoration of adropin signaling by therapeutic application of bioactive adropin34–76 peptides in turn inhibited TGFβ-induced fibroblast activation and fibrotic tissue remodeling in primary human dermal fibroblasts, three-dimensional full-thickness skin equivalents, mouse models of bleomycin-induced pulmonary fibrosis and sclerodermatous chronic graft-versus-host-disease (sclGvHD), and precision-cut human skin slices. Knockdown of GPR19, an adropin receptor, abrogated the antifibrotic effects of adropin in fibroblasts. RNA-seq demonstrated that the antifibrotic effects of adropin34–76 were functionally linked to deactivation of GLI1-dependent profibrotic transcriptional networks, which was experimentally confirmed in vitro, in vivo, and ex vivo using cultured human dermal fibroblasts, a sclGvHD mouse model, and precision-cut human skin slices. ChIP-seq confirmed adropin34–76-induced changes in TGFβ/GLI1 signaling. Our study characterizes the TGFβ-induced down-regulation of adropin/ENHO expression as a potential pathomechanism of SSc as a prototypical systemic fibrotic disease that unleashes uncontrolled activation of profibrotic GLI1 signaling.
CRIS-Team Scopus Importer:2024-04-05

TGFβ promotes fibrosis by MYST1-dependent epigenetic regulation of autophagy - Zehender, Ariella; Li, Yi-Nan; Lin, Neng Yu; Stefanica, Adrian; Nüchel, Julian; Chen, Chih-Wei; Hsu, Hsiao Han; Zhu, Honglin; Ding, Xiao; Huang, Jingang; Shen, Lichong; Györfi, Andrea-Hermina; et al. (Nature Communications, 2021)
Activation of fibroblasts is essential for physiological tissue repair. Uncontrolled activation of fibroblasts, however, may lead to tissue fibrosis with organ dysfunction. Although several pathways capable of promoting fibroblast activation and tissue repair have been identified, their interplay in the context of chronic fibrotic diseases remains incompletely understood. Here, we provide evidence that transforming growth factor-β (TGFβ) activates autophagy by an epigenetic mechanism to amplify its profibrotic effects. TGFβ induces autophagy in fibrotic diseases by SMAD3-dependent downregulation of the H4K16 histone acetyltransferase MYST1, which regulates the expression of core components of the autophagy machinery such as ATG7 and BECLIN1. Activation of autophagy in fibroblasts promotes collagen release and is both, sufficient and required, to induce tissue fibrosis. Forced expression of MYST1 abrogates the stimulatory effects of TGFβ on autophagy and re-establishes the epigenetic control of autophagy in fibrotic conditions. Interference with the aberrant activation of autophagy inhibits TGFβ-induced fibroblast activation and ameliorates experimental dermal and pulmonary fibrosis. These findings link uncontrolled TGFβ signaling to aberrant autophagy and deregulated epigenetics in fibrotic diseases and may contribute to the development of therapeutic interventions in fibrotic diseases.
CRIS-Team Scopus Importer:2021-08-06

X-linked inhibitor of apoptosis protein (XIAP) inhibition in systemic sclerosis (SSc) - Bergmann, Christina; Hallenberger, Ludwig; Chenguiti Fakhouri, Sara; Chenguiti Fakhouri, Sara; Merlevede, Benita; Brandt, Adrian; Dees, Clara; Zhu, Honglin; Zehender, Ariella; Zhou, Xiang; Schwab, Annemarie; Chen, Chih-Wei; et al. (Annals of the Rheumatic Diseases, 2021)
X-linked inhibitor of apoptosis protein (XIAP) is a multifunctional protein with important functions in apoptosis, cellular differentiation and cytoskeletal organisation and is emerging as potential target for the treatment of various cancers. The aim of the current study was to investigate the role of XIAP in the pathogenesis of systemic sclerosis (SSc). The expression of XIAP in human skin samples of patients with SSc and chronic graft versus host disease (cGvHD) and healthy individuals was analysed by quantitative PCR, immunofluorescence (IF) and western blot. XIAP was inactivated by siRNA-mediated knockdown and pharmacological inhibition. The effects of XIAP inactivation were analysed in cultured fibroblasts and in the fibrosis models bleomycin-induced and topoisomerase-I-(topoI)-induced fibrosis and in Wnt10b-transgenic mice. The expression of XIAP, but not of other inhibitor of apoptosis protein family members, was increased in fibroblasts in SSc and sclerodermatous cGvHD. Transforming growth factor beta (TGF-β) induced the expression of XIAP in a SMAD3-dependent manner. Inactivation of XIAP reduced WNT-induced fibroblast activation and collagen release. Inhibition of XIAP also ameliorated fibrosis induced by bleomycin, topoI and overexpression of Wnt10b in well-tolerated doses. The profibrotic effects of XIAP were mediated via WNT/β-catenin signalling. Inactivation of XIAP reduces binding of β-catenin to TCF to in a TLE-dependent manner to block WNT/β-catenin-dependent transcription. Our data characterise XIAP as a novel link between two core pathways of fibrosis. XIAP is overexpressed in SSc and cGvHD in a TGF-β/SMAD3-dependent manner and in turn amplifies the profibrotic effects of WNT/β-catenin signalling on fibroblasts via transducin-like enhancer of split 3. Targeted inactivation of XIAP inhibits the aberrant activation of fibroblasts in murine models of SSc.
CRIS-Team Scopus Importer:2021-05-07
Keywords: fibroblasts; pulmonary fibrosis; scleroderma; systemic